(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: Miscarriage is a major clinical problem in obstetrics with an estimated incidence of around 25% of all pregnancies worldwide. Traditionally, these events are categorized by gestational length: early versus late miscarriage, where early miscarriage is loss of the pregnancy before 12 weeks of completed gestation, and late between 12 and 22 weeks of gestation. Material and Method: At the obstetrics and gynecology hospital in Karbala, Iraq, our study was conducted from December 2024 to May 2025 to determine the demographic characteristics of women with a miscarriage. Study participants answered predesigned questionnaires which included data on sociodemographic and reproductive variables such as; name, age, parity, number of previous miscarriages, educational level, gestational age at presentation and other clinical details. Women with miscarriages who were free of autoimmune diseases had their peripheral blood samples taken. Sera were transferred and stored at −20°C until analysis. The serological tests for Toxoplasma gondii (T. gondii) and cytomegalovirus (CMV) (IgM and IgG antibodies) were performed using enzyme-linked immunosorbent assay (ELISA). Furthermore, microbiological specimens from placental tissues were obtained and the bacterial isolation and characterization were performed by the VITEK® 2 Compact automated system. Results: The present investigation revealed that among patients and control groups, most of the women within age group 20-30 years, and a statistically significant difference was obtained between the both of two cohorts. Twenty (28.6%) of patients were lived in urban areas and the rest 50 (71.4%) of the patients lived in rural areas. Based on the number of previous miscarriages, the highest number was observed in the first group (those with no prior miscarriage), totaling 31 cases (44.3%), and 29 cases (41.4%) in the second group (those with a previous miscarriage). Lowest percent was in the third group, those with two miscarriages, with significant differences. The knowledge level also differed significantly between patients and healthy control women. Microbiological and serological tests demonstrated four different types of infections among studied patients that including: bacterial infections, T. gondii, CMV, and co-infection of T. gondii and CMV. Conclusion: This demographic analysis for studied participants discloses several notable patterns that may participate to the physiological dynamics causing abortion and those women had four different infection kinds including: bacterial infection, T. gondii, CMV, and those who had both T. gondii and CMV.